On the number of zeros of iterated operators on analytic Legendre expansions - Carl Prather (International Journal of Mathematics and Mathematical Sciences)
Let L=(1−z2)D2−2zD, D=d/dz and f(z)=∑n=0∞cnpn(z), with Pn being the nth Legendre polynomial and f analytic in an ellipse with foci ±1. Set Lk=L(Lk−1), k≥2. Then the number of zeros of Lkf(z) in this ellipse is O(klnk).